2021
DOI: 10.3390/ijerph18126492
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers after Controlled Inhalation Exposure to Exhaust from Hydrogenated Vegetable Oil (HVO)

Abstract: Hydrogenated vegetable oil (HVO) is a renewable diesel fuel used to replace petroleum diesel. The organic compounds in HVO are poorly characterized; therefore, toxicological properties could be different from petroleum diesel exhaust. The aim of this study was to evaluate the exposure and effective biomarkers in 18 individuals after short-term (3 h) exposure to HVO exhaust and petroleum diesel exhaust fumes. Liquid chromatography tandem mass spectrometry was used to analyze urinary biomarkers. A proximity exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(65 reference statements)
2
7
0
Order By: Relevance
“…No vehicle in this study had an external NO x reduction unit, and the implementation of one could potentially have reduced the NO x emissions and related health effects. Krais et al [ 25 ] found a small increase in lipid peroxidation (urinary 4-HNE-MA) after the HVO PM+NOx exposure, while Scholten et al [ 26 ] found no genotoxic indications from any of the exposures. From the results in this short-exposure study, we cannot exclude the potential risk of short- and long-term effects from exposure to HVO exhaust, with and without the particle fraction, from modern non-road vehicles that comply with the latest emission standards and the future OELs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No vehicle in this study had an external NO x reduction unit, and the implementation of one could potentially have reduced the NO x emissions and related health effects. Krais et al [ 25 ] found a small increase in lipid peroxidation (urinary 4-HNE-MA) after the HVO PM+NOx exposure, while Scholten et al [ 26 ] found no genotoxic indications from any of the exposures. From the results in this short-exposure study, we cannot exclude the potential risk of short- and long-term effects from exposure to HVO exhaust, with and without the particle fraction, from modern non-road vehicles that comply with the latest emission standards and the future OELs.…”
Section: Discussionmentioning
confidence: 99%
“…However, compared to petroleum diesel the toxicity of these emissions is less evaluated. Only a few controlled human exposure studies of FAME type fuels exist [ 8 , 24 ], but to the best of the authors’ knowledge there are no such studies on HVO except the co-publications concerning this study from Krais et al [ 25 ] and Scholten et al [ 26 ]. In addition, there is only one study that have investigated the acute effect in humans after exposure to diesel exhaust from vehicles with and without an aftertreatment system (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the participants were told to try to live as normal and similar as possible before each exposure session. Previous studies have investigated pulmonary function and self-rated symptoms (Gren et al, 2022 ), urinary PAH metabolites and biomarkers (Krais et al, 2021 ), and genotoxic responses (Scholten et al, 2021 ), respectively, in response to the exposures.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we analyzed for 3-hydroxypropyl mercapturic acid (3-HPMA), a marker for acrolein; 4-hydroxynonenal mercapturic acid (4-HNE-MA), a marker for lipid peroxidation; and 8-oxo-2′-deoxyguanosine (8-oxodG), a marker for DNA damage. Method details are described in Krais et al ( 2021 ) and in Supplemental Information.…”
Section: Methodsmentioning
confidence: 99%
“…Population A study on short-term diesel exhaust exposure (3 h) in which healthy humans were exposed to diesel exhaust, including 7500 ng m −3 PAHs (16 US EPA PAHs (Wierzbicka et al 2014)), in a chamber, did not find urinary PAH metabolites exceeding background levels (Krais et al 2021). Even though the 8 h normalized levels (7500 × 3 h/8) would be similar to those of this study (2700 vs. 1500 ng m −3 of total PAHs in this study), the longer exposure time in this study (i.e., urine collected after 8 h exposure) could cause the increase in urinary PAH metabolites.…”
Section: Studymentioning
confidence: 99%